Caregivers and Babies in Interaction: A Study of Two Families in Wonosobo, Central Java - Kurniawati, Wira; Putri, Clorinda Zakiyya (Allure Journal, 2024)
Parentese in each community has its own characteristics. This study aims to describe the interaction between caregivers and infants with a case study in two Javanese families living in the Wonosobo urban area (mother, babysitter, grandmother, and baby aged 0;4 [K1] and 1;6 [K2]), Central Java. This research used the ethnographic method through observation involving both families. The results showed that knowledge of the competence and cognition ability of the baby became the background for caregivers to adjust themselves so as to create an asymmetrical position. This places the caregiver as the party who "dominates" the interaction. In interaction, elements of caregiver contribution can be done by providing verbal stimuli to the baby, giving verbal responses to the baby's behavior, imitating the baby's behavior, shedding, role-playing as a baby, and inviting the baby to do simple games. Meanwhile, babies contribute to vocalizations and kinesic interactions. This study concluded that various interactions between caregivers and infants in two families in the urban environment of Wonosobo, Central Java are evidence that caregivers include babies in interaction activities. That is, caregivers do not wait for the baby to reach the verbal stage for them to start interacting verbally with the baby.